2021
DOI: 10.3390/pathogens10111360
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicity of Wiped Dust and Airborne Microbes in Individual Classrooms Increase the Risk of Teachers’ Work-Related Symptoms: A Cross-Sectional Study

Abstract: Background: The causes and pathophysiological mechanisms of building-related symptoms (BRS) remain open. Objective: We aimed to investigate the association between teachers’ individual work-related symptoms and intrinsic in vitro toxicity in classrooms. This is a further analysis of a previously published dataset. Methods: Teachers from 15 Finnish schools in Helsinki responded to the symptom survey. The boar sperm motility inhibition assay, a sensitive indicator of mitochondrial dysfunction, was used to measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 124 publications
(197 reference statements)
1
13
0
Order By: Relevance
“…In the present study, symptoms related to indoor air were significantly associated with AD, AR, AC, asthma, and atopic multimorbidity, as in previous studies 21,34 : In Sweden, several indoor air factors, including humid air and mold odor in multifamily houses, associated with eczema, allergy, and asthma 21 . Recently, a study conducted in Finland found that the toxicity of wiped dust and airborne microbes in indoor air at workplace were significantly associated with multiple work‐related respiratory and ocular symptoms 22 . In the same study, the toxicity of wiped dust was significantly associated with AR.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In the present study, symptoms related to indoor air were significantly associated with AD, AR, AC, asthma, and atopic multimorbidity, as in previous studies 21,34 : In Sweden, several indoor air factors, including humid air and mold odor in multifamily houses, associated with eczema, allergy, and asthma 21 . Recently, a study conducted in Finland found that the toxicity of wiped dust and airborne microbes in indoor air at workplace were significantly associated with multiple work‐related respiratory and ocular symptoms 22 . In the same study, the toxicity of wiped dust was significantly associated with AR.…”
Section: Discussionsupporting
confidence: 60%
“… 21 Recently, a study conducted in Finland found that the toxicity of wiped dust and airborne microbes in indoor air at workplace were significantly associated with multiple work‐related respiratory and ocular symptoms. 22 In the same study, the toxicity of wiped dust was significantly associated with AR. This association might be bidirectional as the toxicity of indoor air might predispose to the development of atopic diseases, or individuals with atopic morbidity might be more prone to develop symptoms related to indoor air toxins or microbes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In previous studies, self‐reported allergy like hay fever 36 and atopy 35 increased the risk for reporting SBS. A recent Finnish study found an association between toxicity of classroom dust and airborne microbes and teachers' risk of work‐related respiratory and ocular symptoms 37 . More studies are needed to establish the association between mould exposure and HE.…”
Section: Discussionmentioning
confidence: 99%
“…The BSMI assay measures inability to respond to induction of motility after toxin exposure and has been described in detail previously [ 10 , 57 , 58 ]. Commercially available extended boar semen containing 2.7 × 10 7 sperm cells mL −1 was obtained from Figen Ltd., Tuomikylä, Finland.…”
Section: Methodsmentioning
confidence: 99%